Improving the Tactics of Managing Women in Labor with Soft Tissue Injuries of the Birth Canal (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
We examined 98 postpartum women with injuries of the soft tissues of the birth canal, who were divided into two groups depending on the method of treatment. Postpartum women in the comparison group received generally accepted methods for treating sutures, and the combined drug Depantol was included in the complex of treatment measures for patients in the main group. Depantol contains an antibacterial component and dexpanthenol, which stimulates the regeneration of mucous membranes, normalizes cell metabolism, accelerates mitosis and increases the strength of collagen fibers. The effectiveness of various treatment methods was assessed on the basis of clinical data, laboratory studies of wound secretion, as well as the detection of TLR (toll-like receptors) receptors in blood and wound secretion. The study shows that the inclusion of Depantol in the complex of therapeutic measures provides a more favorable course of the postpartum period and reduces infectious complications.